Intestinal Epithelial Cells and the Microbiome Undergo Swift Reprogramming at the Inception of Colonic Citrobacter rodentium Infection - Hopkins, Eve G. D. (mBio, 2019)
We used the mouse attaching and effacing (A/E) pathogen Citrobacter rodentium, which models the human A/E pathogens enteropathogenic Escherichia coli and enterohemorrhagic E. coli (EPEC and EHEC), to temporally resolve intestinal epithelial cell (IEC) responses and changes to the microbiome during in vivo infection. We found the host to be unresponsive during the first 3 days postinfection (DPI), when C. rodentium resides in the caecum. In contrast, at 4 DPI, the day of colonic colonization, despite only sporadic adhesion to the apex of the crypt, we observed robust upregulation of cell cycle and DNA repair processes, which were associated with expansion of the crypt Ki67-positive replicative zone, and downregulation of multiple metabolic processes (including the tricarboxylic acid [TCA] cycle and oxidative phosphorylation). Moreover, we observed dramatic depletion of goblet and deep crypt secretory cells and an atypical regulation of cholesterol homeostasis in IECs during early infection, with simultaneous upregulation of cholesterol biogenesis (e.g., 3-hydroxy-3-methylglutaryl–coenzyme A reductase [Hmgcr]), import (e.g., low-density lipoprotein receptor [Ldlr]), and efflux (e.g., AbcA1). We also detected interleukin 22 (IL-22) responses in IECs (e.g., Reg3γ) on the day of colonic colonization, which occurred concomitantly with a bloom of commensal Enterobacteriaceae on the mucosal surface. These results unravel a new paradigm in host-pathogen-microbiome interactions, showing for the first time that sensing a small number of pathogenic bacteria triggers swift intrinsic changes to the IEC composition and function, in tandem with significant changes to the mucosa-associated microbiome, which parallel innate immune responses.